Durability is improved by both low and high intensity endurance training - Matomäki, Pekka; Heinonen, Olli J.; Nummela, Ari; Laukkanen, Jari; Auvinen, Eero-Pekka; Pirkola, Leena; Kyröläinen, Heikki (Frontiers in Physiology, 2023)
Introduction: This is one of the first intervention study to examine how low- (LIT) and high-intensity endurance training (HIT) affect durability, defined as ‘time of onset and magnitude of deterioration in physiological-profiling characteristics over time during prolonged exercise’. Methods: Sedentary and recreationally active men (n = 16) and women (n = 19) completed either LIT (average weekly training time 6.8 ± 0.7 h) or HIT (1.6 ± 0.2 h) cycling for 10 weeks. Durability was analyzed before and after the training period from three factors during 3-hour cycling at 48% of pretraining maximal oxygen uptake (VO2max): 1) by the magnitude and 2) onset of drifts (i.e. gradual change in energy expenditure, heart rate, rate of perceived exertion, ventilation, left ventricular ejection time, and stroke volume), 3) by the ‘physiological strain’, defined to be the absolute responses of heart rate and its variability, lactate, and rate of perceived exertion. Results: When all three were averaged the durability was improved similarly (time x group p = 0.42) in both groups (LIT: p = 0.03, g = 0.49; HIT: p = 0.01, g = 0.62). In the LIT group, magnitude of average of drifts and their onset did not reach statistically significance level of p < 0.05 (magnitude: 7.7±6.8% vs. 6.3±6.0%, p = 0.09, g = 0.27; onset: 106±57 min vs. 131±59 min, p = 0.08, g = 0.58), while averaged physiological strain improved (p = 0.01, g = 0.60). In HIT, both magnitude and onset decreased (magnitude: 8.8±7.9% vs. 5.4±6.7%, p = 0.03, g = 0.49; onset: 108±54 min vs. 137±57 min, p = 0.03, g = 0.61), and physiological strain improved (p = 0.005, g = 0.78). VO2max increased only after HIT (time x group p < 0.001, g = 1.51). Conclusion: Durability is improved similarly by both LIT and HIT based on reduced physiological drifts, their postponed onsets, and changes in physiological strain. Despite durability enhanced among untrained people, a 10-week intervention did not alter drifts and their onsets in a large amount, even though it attenuated physiological strain.